Aplikasi Game Edukasi 2D Pengenalan Bahasa Daerah Toraja Untuk Anak Sekolah Dasar - Mokoginta, Hendra S.; Tulenan, Virginia; Sugiarso, Brave A. (Jurnal Teknik Informatika, 2019)
Abstract — Toraja residents rarely use local languages as a daily language but use Indonesian or other languages, especially elementary school children. The results of the question and answer with 30 respondents to choose the correct Toraja language, the respondents who answered correctly were around 40% and those who answered incorrectly were 60%. After being seen, an educational game application was created which aimed to introduce Toraja to elementary school children. This game has an educational genre using the Extreme Programming (XP) design method and can be run on the Android platform. After doing the implementation of this application, an increase of about 97% was answered correctly. Keywords — Educational Game; Elementary School Children ; Extreme Programming (XP); Toraja Language;. Abstrak — Penduduk Toraja sudah jarang menggunakan bahasa daerahnya sebagai bahasa sehari-hari namun menggunakan bahasa Indonesia ataupun bahasa asing, terlebih lagi anak sekolah dasar. Hasil tanya jawab dengan 30 responden untuk memilih manakah bahasa Toraja yang benar, responden yang menjawab benar sekitar 40% dan yang menjawab salah sebanyak 60%. Setelah diamati maka dibuatlah aplikasi game edukasi yang bertujuan untuk mengenalkan bahasa daerah Toraja kepada anak sekolah dasar. Game ini mempunyai genre edukasi dengan menggunakan metode perancangan Extreme Programming(XP) serta dapat dijalankan pada platform Android. Setelah melakukan implemantasi apliaksi ini, terdapat pengingkatan sekitar 97% menjawab benar dan 3% menjawab salah. Kata kunci — Anak Sekolah Dasar; Bahasa Daerah Toraja; Extreme Programming (XP); Game Edukasi.